Analyzing Trump and Pence's CRT Speeches Using the Ideological Square - Wibowo, Joko (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
The research analyzed how Donald Trump and Mike Pence applied van Dijk’s Ideological Square to portray their group positively and CRT negatively in political speeches. This research demonstrates how language can influence public opinion and obscure key facts about racism and justice. The study employed descriptive qualitative methods, utilizing van Dijk’s Ideological Square, to analyze speeches by Donald Trump and Mike Pence regarding Critical Race Theory (CRT). The data were obtained from the official transcript, and the analysis involved categorizing words and sentences to reveal ideological strategy and public influence. They praised their group, criticized the opponents, concealed America’s faults, and overlooked the positive aspects of CRT. Through this strategy, they built a positive image of their group while forming a negative public opinion of CRT. Language was used to influence emotion, trust, and public understanding. This research contributed to an understanding of political language and ideology in speech.